Identifying New Zealand, Southeast Australia, and Southwest Pacific historical weather data sources using Ian Nicholson's Log of Logs. (19th June 2013) - Chappell, Petra R.; Lorrey, Andrew M.
<x xml:space="preserve">Abstract</x> Historical meteorological data are essential for increasing the level of understanding about past, present, and future climates. In the Northern Hemisphere, a significant amount of research has been dedicated to rescuing climate data from historical sources such as ship logbooks (e.g. RECLAIM, CLIWOC, and ICOADS). However, limited research in this field has focused on New Zealand, Southeast Australia, and the Southwest Pacific. Because these regions were colonized recently by Europeans (~200 years ago), only 50–100 years of land‐based meteorological data exist for many locations. However, meteorological information contained in ship logbooks may extend and reinforce the existing historical climate record for these regions. The Log of Logs is a catalogue of ships that visited Australia, New Zealand, and surrounding waters in the th and 20th centuries of the Common Era. These volumes provide a record of the location of ship logbooks. This study extracted information from the Log of Logs for New Zealand, Southeast Australia, and the Southwest Pacific for 1786–1900. The purpose of this was to locate ship logbooks that may contain meteorological data. The next stage of this project is to gather, image, digitize, and to analyse the data from the prioritized logbooks. These data have application for local climate reconstruction, extension of regional circulation indices, and augmentation of the extended reanalysis without radiosondes effort.